Charcuterie : the craft of salting, smoking, and curing - Ruhlman, Michael, 1963- (W.W. Norton & Company, 2013)
In addition to providing 125 classic recipes for sausages, terrines, and pates, the authors expand the definition of "charcuterie" to include anything preserved or prepared ahead such as Mediterranean olive and vegetable rillettes, duck confit, and pickles and sauerkraut.